Fluoretos em odontologia: Entre a saúde e a doença - Efigenia Ferreira e Ferreira (2000)
The fluoride used in dental caries control, can bring the expected benefits but can also cause problems on the form of fluorosis. This work aimed to analyze the benefits and burdens of fluoride in minicipio Resende Costa - MG, fluoridated since 1981 and with the collective programs (SUS), in operation for six years. We examined 292 children at ages 7, 12 and 15 years, groups formed according to the greater or less concicio with fluorine. The results showed 74.4% (7 years), 20% (12 years) and 15.46% (15 years) of caries-free (KW, p = 0.000 adjusted t = 0.000) and prevalence of fluorosis of 74, 4% (7 years), 66.7% (12 years) and 78.4% (15 years) (KW, p = 0.359). The mean DMFT was 2.25, and 2.63 to 12 years, meaning the achievement of the goal proposed by WHO. However, there was the impossibility of improvement in this context with the methods used so far. It is therefore the need to work with the qualitative methodology as well as how to ensure better health for this population, the possibility of a healthier adult population, considering how fundamental changes in behavior. It concludes the reorganization of health services and intersectoral way, besides the existing quantitative assessment, the use of qualitative assessment as a means of better targeting strategies to